Threat of Data Theft (Phishing) Amid Trends in Fintech Users During the Covid-19 Pandemic (Study Phishing In Indonesia) - Fitri Nur Latifah; Imron Mawardi; Bayu Wardhana (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of this research is to find out the extent of the crime of data theft (phishing) in fintech and how to anticipate it in Indonesia in the midst of the Coronavirus Pandemic that has hit Indonesia in recent years. The COVID-19 pandemichas had an impact on all community activities. The existence of social distancing and physical distancing policies has made changes to community activities, including financial services. The use of technology-based financial services or what is often termed financial technology has now become a trend and habit in the community. The literature review research method that we use in this study uses sources from several literacies such as books, journal articles, media reports and so on.The results of this study that phishing is currently found in several models of crimeand there are several efforts to prevent this crime from becoming more widespread.